Bericht über anthropogeographische Studien in Südäthiopien - Kuls, Wolfgang (ERDKUNDE, 1956)
The author of this report was able to spend one year in the lake region of southern Ethiopia as the geographer of an expedition carried out by the FrobeniusInstitute of Frankfurt-am-Main University. During longer sojourns within various tribal areas, he studied their human geography. For that purpose a classification of the different tribes into MUSA ENSETE growers, millet growers and pastoralists was found practicable. The main areas where Ensete is grown show a high population density, 100 to 150 people per sq. Km. are frequently found, and holdings are mostly between 0.5 and 1 hectare in size. The link between Ensete cultivation and manuring is very likely of recent origin. Shifting cultivation must be assumed to be the original method and some traces of this can still be recognised. The former area of distribution of Ensete has been reduced as a result of the migration of the Galla, but areas where einzelhöfe dominate today must not be taken to indicate areas of form er Ensete cultivation. lt was possible to observe the emergence of einzelhöfe during the change over from pure animal husbandry to cultivation in the tribal area of the Arussi. Many diversities within areas of Ensete cultivation are due partly to physical factors but partly without doubt to factors of the social geography. The millet growers, with their large villages, impressive retrace cultivation and many peculiar crops seemingly form a group which is distinctly separated from the other inhabitants of the lake region. However, all their peculiar characteristics can be found represented elsewhere in the investigated area. Of prime importance for the economic existence of the millet growers are the uncertain conditions of precipitation in their habitat on the southern fringe of the Ethiopian highland. Many features are clearly meant to overcome this uncertainty in the food supply which results from these conditions. Particularly interesting in this connection is the regular planting of some tubers which serve as emergency food should the millet harvest be insufficient. The lake region has been influenced considerably through conquest by the Amhari and through the Italian occupation. An important fact is the pacification of the country which had many consequences, in particular for the pastoralists. The introduction of the Amharian plough cultivation, which is found here and there, has not wrought great changes, nor is it now considered to be the deciding cause of the widespread soil erosion.